1998
DOI: 10.1037/0735-7044.112.5.1152
|View full text |Cite
|
Sign up to set email alerts
|

Elevated novelty seeking and peculiar d-amphetamine sensitization in periadolescent mice compared with adult mice.

Abstract: Novelty seeking as well as amphetamine sensitization were studied in adult (postnatal day "PND" > 60) and periadolescent (PND 3343) mice treated with saline or amphetamine (2 or 10 mg/kg once per day) for 3 days in a familiar environment. After a 48-hr wash-out period, mice were challenged with either saline or amphetamine (2 mg/kg) in the same environment. When given a choice, animals showed a preference for a novel environment, an effect more marked in periadolescents. Acute amphetamine strongly increased no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
167
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 43 publications
12
167
0
2
Order By: Relevance
“…Forced exposure to novelty is generally stressful to rodents (Hennessy et al 1979;Misslin et al 1982), whereas, under free-choice conditions, periadolescent rodents are known to be characterized by a marked preference for novelty (Adriani et al 1998;Laviola et al 1999;Spear 2000). Hence, it is possible to hypothesize that an age-related discontinuity in the response to the novel taste of nicotine emerged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Forced exposure to novelty is generally stressful to rodents (Hennessy et al 1979;Misslin et al 1982), whereas, under free-choice conditions, periadolescent rodents are known to be characterized by a marked preference for novelty (Adriani et al 1998;Laviola et al 1999;Spear 2000). Hence, it is possible to hypothesize that an age-related discontinuity in the response to the novel taste of nicotine emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Periadolescent rodents differ markedly from adults in their spontaneous behavioral repertoire (Cirulli et al 1996;Terranova et al 1993;Meaney and Stewart 1981;Panksepp 1981). In fact, elevated levels of novelty seeking and a reduced behavioral and hormonal response to stress (Adriani et al 1998;Adriani and Laviola 2000) are exhibited by animals around this age. A characteristic hyporesponsivity to the effects of an acute administration of psychostimulants (Spear and Brake 1983;Laviola et al 1995;Bolanos et al 1998;Adriani and Laviola 2000), a peculiar pattern of behavioral sensitization following repeated drug exposure (Laviola et al 1995(Laviola et al , 2001Adriani et al 1998), as well as a weak drug-induced place conditioning profile (Adriani et al 1998;Bolanos et al 1996Bolanos et al , 1998; but see Campbell and Spear 2000), are also reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study (Kozanian, Gutierrez, Mohd‐Yusof, & McDougall, 2012) found, albeit using stimulants other than AMPH or MPH, a sensitized response to the repeated administration of methamphetamine or cocaine in preweanling, but not in adolescent, rats. Conversely, adolescent but not adult mice exhibited greater motor activity to a challenge dose of AMPH (2.0 mg/kg), after a history of exposure to 10.0 mg/kg AMPH (Adriani et al., 1998). It has been suggested that the mechanisms responsible for the expression of long‐term sensitization to psychostimulants are just concluding maturation by the fourth week of rats’ postnatal life (Tirelli, Laviola, & Adriani, 2003), which could explain the variability in the reported results.…”
Section: Discussionmentioning
confidence: 99%
“…On PD33, they were all challenged with a lower dose [2.0 mg/kg, based on work by Adriani, Chiarotti, and Laviola (1998)] than that used during the induction phase. Forty of these animals ( n  = 10 per group) were assessed for motor activity after each administration and subsequently, on PDs 35, 37, and 39, were tested for ethanol intake.…”
Section: General Methodsmentioning
confidence: 99%